Analysis of microstructure eutectic Tb3Sc2Al3O12-TbScO3 photonic properties - Mossakowska-Wyszynska, Agnieszka; Kaczkan, Marcin; Koba, Marcin; Pawlak, Dorota; Kołodziejak, Katarzyna; Turczyński, Sebastian (Photonics Letters of Poland, 2011)
In this paper, a numerical analysis of self-organized microstructured dielectric eutectic photonic crystal properties is presented. In particular, we study the terbium-scandium-aluminum garnet - terbium-scandium perovskite structure Tb3Sc2Al3O12-TbScO3, grown by the micro-pulling down method. The self-organized dielectric microstructure is made of perovskite fibers embedded in a garnet phase matrix. In general, we analyzed the distribution of the electromagnetic field in the investigated periodic structures and the existence of a photonic band gap of such photonic crystals as a function of eutectic geometric parameters. Investigated structures do not reveal a wide photonic band gap, because of the low contrast of the refractive indices of individual phases. Full Text: PDF References: E. Yablonowitch, "Inhibited Spontaneous Emission in Solid-State Physics and Electronics", Phys. Rev. Lett. 58, 2059 (1987). [CrossRef] J.B. Pendry, "Negative Refraction Makes a Perfect Lens", Phys. ReV. Lett. 85, 3966 (2000). [CrossRef] D.A. Pawlak, K. Kolodziejak, S. Turczynski, J. Kisielewski, K. Rozniatowski, R. Diduszko, M. Kaczakn, M. Malinowski, "Self-Organized, Rodlike, Micrometer-Scale Microstructure of Tb3Sc2Al3O12-TbScO3:Pr Eutectic", Chem. Matter. 18, 2450 (2006). [CrossRef] D.A. Pawlak, Scientia Plena 4, 014801 (2008). [DirectLink] K. Postava, L. Halagacka, D. Hrabovsky, O. Zivotsky, J. Pistora, D.A. Pawlak, S. Turczynski, K. Kolodziejak, "Optical spectroscopy of terbium-scandium-aluminium garnet and terbium-scandium perovskite", Proc. SPIE 7353, 735311 (2009). [CrossRef] S.G. Johnson, J.D. Joannopoulos, The MIT Photonic-Bands Package, [DirectLink] S.G. Johnson, J.D. Joannopoulos, "Block-iterative frequency-domain methods for Maxwell's equations in a planewave basis", Opt. Exp. 8 173 (2001), [CrossRef]